2017
DOI: 10.5539/jmsr.v6n4p96
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Activity on Protease Adsorbed on Biochar in Organic Solvents

Abstract: We have found that the organic solvent-resistance of α-chymotrypsin (α-CT) is enhanced by adsorbing α-CT onto bamboo charcoal powder (BCP), which is obtained by pyrolyzing bamboo waste under nitrogen atmosphere, and is markedly dependent on the thermodynamic water activity (a w ) in organic solvents. When BCP-adsorbed α-CT was immersed in acetonitrile at an appropriate water activity, it effectively enhanced the transesterification of Nacetyl-L-tyrosine ethyl ester (N-Ac-Tyr-OEt) with n-butanol (BuOH) to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Moreover, it is suggested that the content of functional groups in bamboo charcoal is suitable to keep the secondary structure of α-CT in acetonitrile since functional groups contribute to the adsorption of α-CT on biochar. Figure 17 shows time course of remaining activities of free α-CT and bamboo charcoal-adsorbed α-CT through the heat treatment at 50°C [20]. The state of free α-CT in acetonitrile, where α-CT was dispersed as the solid state, was unchanged during the heat treatment, although enzymes dissolved in an aqueous solution immediately form the aggregation of thermally denatured enzymes [15].…”
Section: Organic Solvent Stress Tolerance Of Enzymes Adsorbed On Biocharmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is suggested that the content of functional groups in bamboo charcoal is suitable to keep the secondary structure of α-CT in acetonitrile since functional groups contribute to the adsorption of α-CT on biochar. Figure 17 shows time course of remaining activities of free α-CT and bamboo charcoal-adsorbed α-CT through the heat treatment at 50°C [20]. The state of free α-CT in acetonitrile, where α-CT was dispersed as the solid state, was unchanged during the heat treatment, although enzymes dissolved in an aqueous solution immediately form the aggregation of thermally denatured enzymes [15].…”
Section: Organic Solvent Stress Tolerance Of Enzymes Adsorbed On Biocharmentioning
confidence: 99%
“…Similarly, the catalytic activity of biochar-adsorbed enzymes might be influenced in hydrophilic organic solvents containing low water content. Figure 18 shows the relationship of the initial transesterification rate (V e ) and the initial hydrolysis rate (V h ) with the water activity in acetonitrile at 25°C [20]. Low water activity inhibited the inherent enzymatic hydrolysis of N-acetyl-L-tyrosine ethyl ester (N-Ac-Tyr-OEt) with water, whereas the enzymatic transesterification of N-acetyl-L-tyrosine ethyl ester (N-Ac-Tyr-OEt) with n-butanol (BuOH) was enhanced.…”
Section: Organic Solvent Stress Tolerance Of Enzymes Adsorbed On Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare bamboo charcoal as a biochar, under a nitrogen atmosphere, bamboo waste was dried at 180 0 C for 2 h, was pyrolyzed at 450 0 C for 2 h, was carbonized at 350 0 C for 3 h, and then was cooled at 100 0 C for 1 h by pyrolyzer (EE21 Pyrolyzer, EEN Co. Ltd., Japan) (Noritomi et al, 2017b). Bamboo charcoal powder (BCP) was obtained by grinding the resultant bamboo charcoal with a jet mill (100AS, Fuji Sangyo Co. Ltd., Japan).…”
Section: Preparation Of Bamboo Charcoal Powdermentioning
confidence: 99%
“…In order to apply forestry residues to enzyme carriers, we have so far examined the catalysis of enzymes adsorbed on bamboo charcoal powder (BCP), which was prepared from forestry residues by pyrolysis. We have reported that the adsorption of enzymes on BCP markedly improve the catalytic activity of enzymes in organic solvents (Noritomi et al, 2017a;Noritomi et al, 2017b;Noritomi et al, 2018). In this study, we have examined the stability of enzymes adsorbed on BCP in an aqueous solution at high temperatures.…”
Section: Introductionmentioning
confidence: 99%